Advances in the Extraction, Modification and Application of Sesame Protein - Ying HOU; Yu PENG; Jianxiong HAO; Dandan ZHAO (Shipin gongye ke-ji)
Due to the increasingly environmental concerns, the surge in global food demand, and the evolving dietary preferences of consumers, there is a growing demand for plant-based protein alternatives. Sesame, abundant in high-quality oils and proteins, is mainly used for oil extraction. The resulting by-product, sesame cake (meal), is rich in sesame protein free from anti-nutritional factors. Unfortunately, it is commonly used in feed and fertilizer production, failing to harness its potential for high-value utilization. This comprehensive review delves into the research advancements in the extraction, modification, and applications of sesame protein. Considering the protein denaturation that may occurs during oil extraction and processing, the paper emphasizes the critical factors in selecting extraction methods for same protein and explores the potential of physical, chemical, and biological approaches to improve extraction efficiency and functionality. Furthermore, the paper suggests a strategic direction for sesame protein to gain a stronger foothold in the plant-based protein alternative market, which includes focused research on modification tailored to specific application needs, studying the interaction mechanisms between sesame protein and other macromolecules in food systems, and the transitioning from laboratory-scale research to industrial production. The goal of this study is to pave new avenues for the high-value processing of sesame meal and to facilitate the widespread application and market penetration of sesame protein as an innovative plant-based protein alternative in the food industry, contributing novel insights and strategies to the sustainable growth of China's distinctive plant-based food industry.